2022
DOI: 10.1186/s13287-022-02879-z
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a novel xeno-free culture medium for human-induced pluripotent stem cells

Abstract: Background Human-induced pluripotent stem cells (hiPSCs) are considered an ideal resource for regenerative medicine because of their ease of access and infinite expansion ability. To satisfy the sizable requirement for clinical applications of hiPSCs, large-scale, expansion-oriented, xeno-free, and cost-effective media are critical. Although several xeno-free media for hiPSCs have been generated over the past decades, few of them are suitable for scalable expansion of cultured hiPSCs because of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…In contrast, the OPUiD04-B line maintained in mTeSR Plus showed significantly reduced OCT3/4 expression compared to that maintained in StemFit. In humans, it is reported that the expression levels of pluripotency markers including OCT3/4 varied among hPSC culture conditions [ 16 ]. The expression levels of pluripotency markers such as OCT3/4 in ciPSCs may also be affected by culture conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the OPUiD04-B line maintained in mTeSR Plus showed significantly reduced OCT3/4 expression compared to that maintained in StemFit. In humans, it is reported that the expression levels of pluripotency markers including OCT3/4 varied among hPSC culture conditions [ 16 ]. The expression levels of pluripotency markers such as OCT3/4 in ciPSCs may also be affected by culture conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The differentiation of hiPSC into hiPSC-CM in the VTN-N-based XF differentiation media induced rapid and synchronized beating activities in the CM, as compared to that achieved with Matrigel TM -based XC differentiation. It has been reported that stem cell expandability and its differentiation can be affected by components of culture media and scaffold, specifically in human stem cells ( 30 , 31 ), and hiPSC-CM ( 32 , 33 ). Our findings also suggest the importance of selecting appropriate scaffold matrix materials during differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Human iPSCs (hiPSCs) were maintained and differentiated according to an established protocol [ 42 , 52 ]. After maintaining the hiPSCs culture in Knockout Serum Replacement (KOSR) medium for 7 days, embryoid bodies (EB) formed, and they were transferred onto the gelatin (0.1%) coated plates.…”
Section: Methodsmentioning
confidence: 99%